Editorial - Tatnall , Arthur (Journal of Law and Governance, 2008)
This is the first issue in the third year of publication of the Journal of Business Systems, Governance and Ethics. As usual the articles included cover a wide range of topics and come from a spread of different countries; in this case Belgium, the United States of America, Australia and Malaysia.